Assessing the readiness of precision medicine interoperability: an exploratory study of the National Institutes of Health Genetic Testing Registry. Issue 4 (1st October 2017) - Ronquillo, Jay G.; Weng, Chunhua; Lester, William T.
Abstract : Background: Precision medicine involves three major innovations currently taking place in healthcare: electronic health records, genomics and big data. A major challenge for healthcare providers is, however, understanding the readiness for the practical application of initiatives like precision medicine. Objective: To better understand the current state and challenges of precision medicine interoperability using a national genetic testing registry (GTR) as a starting point, placed in the context of established interoperability formats. Methods: We performed an exploratory analysis of the National Institutes of Health GTR. Relevant standards included Health Level Seven International Version 3 Implementation Guide for Family History, the Human Genome Organization Gene Nomenclature Committee (HGNC) database and Systematised Nomenclature of Medicine – Clinical Terms (SNOMED CT). We analysed the distribution of genetic testing laboratories, genetic test characteristics and standardised genome/clinical code mappings, stratified by laboratory setting. Results: There were a total of 25, 472 genetic tests from 240 laboratories testing for approximately 3, 632 distinct genes. Most tests focused on diagnosis, mutation confirmation and/or the risk assessment of germline mutations that could be passed to offspring. Genes were successfully mapped to all HGNC identifiers, but less than half of tests were mapped to SNOMED CT codes, highlighting significant gaps when linking genetic tests to standardised clinical codes that explain the medical motivations behind test ordering. Conclusion: While precision medicine could potentially transform healthcare, successful practical and clinical applications will first require the comprehensive and responsible adoption of interoperable standards, terminologies and formats across all aspects of the precision medicine pipeline.